NGHIÊN CỨU DI TRUYỀN LOÀI CHÒ NÂU (Dipterocarpus retusus) Ở PHÚ THỌ PHỤC VỤ CÔNG TÁC BẢO TỒN VÀ CHỌN GIỐNG - Nguyễn, Phan Lan Hồng; Vũ, Đình Duy; Nguyễn, Thị Phương Trang; Nguyễn, Minh Đức; Vũ, Đình Giáp; Bùi, Xuân Phương; Nguyễn, Minh Tâm (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
GENETIC VARIABILITY OF THE SPECIES Dipterocarpus retusus IN PHU THO: CONSERVATION AND BREEDING PROGRAM Dipterocarpus retusus is a valuable wood tree in the tropical forests of northern Vietnam, which is in danger of extinction due to habitat degradation and overexploitation. To date, this species has not been studied. In the present study, the genetic diversity and structure in four populations in Phu Tho province were investigated using microsatellites. A total of 23 alleles were identified, of which three were private alleles. The number of alleles per locus, effective alleles, observed and expected heterozygosity were 2.3, 1.5, 0.265, and 0.287, respectively. The lowest genetic diversity was found in the Chan Mong population, with an effectivealleles of 1.2, an observed heterozygosity of 0.153, and an expected heterozygosity of 0.16. A high inbreeding coefficient was found in Minh Phu (0.225). Genetic differentiation between populations was low (0.135) and gene flow was high (2.759). Habitat degradation can also decrease gene flow. Clustering analyses (Bayensia and Neighbor-joining) revealed three genetic clusters related to geographical distance and disturbed habitats. These results recommend the conservation and restoration of D. retusus in the future.